The Influence of Social Media Marketing, Electronic Word of Mouth, and Brand Image through Social Media TikTok on Purchase Intention of Lafiye Hijab Products - Tsaqifah, Zafira; Rahmawati, Lilla (Proceeding International Conference on Information Technology and Business, 2023)
The purpose of this study was to investigate the impact of Social Media Marketing, Electronic Word of Mouth, and Brand Image on consumer purchase intention for Lafiye Hijab products through Tiktok on social media. This condition has led to increasingly fierce competition in the fashion industry. The research methods used in this research are quantitative methods. The number of samples used in this study were 100 respondents. Data collection was carried out using a questionnaire distributed online to Lafiye Hijab consumers in Indonesia. The analytical technique used is multiple linear with the help of SPSS to determine whether there is a positive relationship between Social Media Marketing, Electronic Word of Mouth, and Brand Image on consumer purchasing intention for Lafiye Hijab products.Keywords— Social Media Marketing, E-WOM, Brand Image, Purchase Intention, Tiktok